EMPOWERED FEMININITY: THE EVOLUTION OF FEMALE STRENGTH IN DISNEY’S MOANA - Galuh Citra Julia Pramesty; Nurhidayat Nurhidayat (Lire Journal (Journal of Linguistics and Literature), 2025)
This research examines how the animated film Moana (2016) by Disney illustrates the concept of empowered femininity through a liberal feminist lens, particularly drawing on Betty Friedan’s theoretical framework. The study analyzes how Moana, as the central character, challenges conventional portrayals of women in media by embodying traits such as independence, leadership, and emotional strength. Using qualitative content analysis, the research identifies Moana’s narrative as a departure from traditional Disney princess tropes, highlighting her journey as one driven by self-determination rather than romantic or male-driven motives. Moana stands out as a proactive and capable figure who redefines what it means to be a female hero in popular culture. Her role as a decision-maker and voyager showcases a shift in gender representations, aligning with liberal feminist ideals that emphasize equal opportunity, personal agency, and the rejection of limiting gender roles. The study also considers how supporting characters and the storyline reinforce these themes, painting a fuller picture of feminine empowerment. Ultimately, the film serves as an example of evolving gender narratives in children's media, presenting a progressive image of femininity that aligns with the goals of liberal feminism.